MODEL PENGUATAN AGAMA MELALUI BUDAYA RELIGIUS SEKOLAH - Nurits Tsuroyya; Makhmudatul Mustagfiroh; Ulfah Rahmawati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Today, the weakness of religious values, especially in students urges the need for an emphasis on religiosity, especially in the school environment. Because with the weakness of this religious spirit, students can easily sway the power of faith, and the death of sympathy and empathy. The model of strengthening religious education through the religious culture of schools aims to provide religious strength which is ultimately embedded in students. This article uses a qualitative research approach with data collection techniques using the literature review method. Analysis of the model of strengthening religious education through the religious culture of schools using the approach of moral knowing, moral feeling, and moral action. With the implementation of the model of strengthening religion through the school's religious culture, it will produce students who are moral, spiritually strong, of character and culture.